Study of the toxic and genotoxic activity of water of lake Kolsai, located on the territory of the Almaty region of the Republic of Kazakhstan (ҚазҰУ хабаршысы. Экология сериясы, 2022)
An important step in assessing the state of natural environment is the identification of various environmentally hazardous factors that possess toxic, genotoxic and mutagenic activity. The appearance in the environment of a new pollutants and an increase in the concentration of already present physicochemical components that exhibit toxic and genotoxic properties contribute to environmental mutational load on biota. In recent decades, due to the intensification of economic activity and the development of the tourism sector, the anthropogenic load has significantly increased not only on terrestrial, in particular mountain ecosystems, but also on natural water reservoirs. In this regard, the purpose of this study was to investigate the genotoxic, mutagenic and toxic activity of surface water of the freshwater lake Nizhny Kolsai, located on the territory of national park "Kolsai kolderi" in the Kegen district of the Almaty region, Republic of Kazakhstan. For the first time, using a number of test systems (DNA comet method, cytogenetic test for accounting for chromosomal aberrations and biochemical analysis of lipid peroxidation products), water samples taken in 2018 and 2022 (spring-summer period) were studied at the Mus musculus model facility. It was found that water samples induced DNA breaks in cells of bone marrow and spleen of experimental mice, the level of which was significantly higher than in intact animals (p